The Impact of Perceived Ease of Use and Financial Self-Efficacy on Financial Loyalty: The Mediating Role of Trust - Niken Amelia; Mardiyani (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to examine the effects of perceived ease of use and financial self-efficacy on financial loyalty, with trust as a mediating variable, among Generation Z digital bank customers in Cirebon. A quantitative approach was employed using an online survey with 150 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results show that perceived ease of use and financial self-efficacy positively influence trust and financial loyalty. Trust is also found to mediate these relationships. These findings imply that improving system usability and financial capability can strengthen customer trust and enhance loyalty in digital banking.